The relationship between accounting teachers professional identity and performance mediated by Teachers Work Engagement - M.Fahmi Johan Syah (2023)
The purpose of this study is to analyse the relationship between ATPI and Accounting Teacher Performance (ATP) mediated by Teachers Work Engagement (TWE) in Central Java, Indonesia. Questionnaires were used to analyse the relationship and data were obtained from 150 (EFA analysis) and 351 (SEM analysis) accounting teachers. Relied on the identity theory, The Structural Equation Modeling (SEM) technique was utilized to perform construct validity, reliability, exploratory factor analysis (EFA), confirmatory factory analysis (CFA), and the relation among variables. The EFA confirms that the Accounting Teachers Professional Identity (ATPI) consist of five constructs namely Cultural Knowledge (CK), Blending (B), Identity Experiencing (IE), Inter-Personal Skill (IPS), and Active in Professional Communities (APC). All the direct effect was significant, ATPI and TWE (= 0.924, p= 0.001), TWE and ATP (= 0.842, p= 0.001), ATPI and ATP (= 0.590, p= 0.000). While the mediating effect between ATPI and ATP through TWE was also significant (= 0.804, p= 0.001) with a statistically proven that TWEs role is a partial mediator. This study concludes that accounting teachers performance can be improved significantly if the accounting teachers and the stakeholders consider the ATPI which has five constructs as a prominent factor that should be strengthened. The improvement will be more significant if the accounting teachers have a good work engagement with the characteristics of vigor, dedication and absorption. The implication of the study provides valuable groundwork for further studies on the improvement of accounting teacher performance through professional identity and work engagement among Indonesian accounting teachers.